Ceria Nanoparticles Synthesized With Aminocaproic Acid for the Treatment of Subarachnoid Hemorrhage. Issue 12 (December 2018) - Jeong, Han-Gil; Cha, Bong Geun; Kang, Dong-Wan; Kim, Do Yeon; Ki, Seul Ki; Kim, Song I.; Han, Ju hee; Yang, Wookjin; Kim, Chi Kyung; Kim, Jaeyun; Lee, Seung-Hoon
Abstract : Background and Purpose—: Despite early aneurysm repair and aggressive management for complications, subarachnoid hemorrhage (SAH) results in at least 25% mortality rate and 50% persistent neurological deficit. We investigated whether ceria nanoparticles which have potent antioxidative activities can protect against subarachnoid hemorrhage via attenuating fatal brain injuries. Methods—: Uniform, 3 nm, water-dispersed ceria nanoparticles were prepared from short sol-gel reaction of cerium (III) ions with aminocaproic acid in aqueous phase. SAH was induced by endovascular perforation of middle cerebral artery of rats. A single dose of ceria nanoparticles (0.5 mg Ce/kg) or saline control was randomly administered intravenously at an hour post-SAH. Neuronal death, macrophage infiltration, SAH grade, and brain edema were evaluated at 72 hours. Mortality and neurological function were assessed for 14 days. Results—: The obtained ceria nanoparticles with high Ce 3+ to Ce 4+ ratio demonstrated potent antioxidative, cytoprotective, and anti-inflammatory activities in vitro. In rodent SAH models, the severity of hemorrhage was comparable between the ceria nanoparticles- and saline-treated groups. However, ceria nanoparticles significantly reduced neuronal death, macrophage infiltration, and brain edema after SAH. Ceria nanoparticles successfully improved survival rates (88.2% in the ceria nanoparticles group versus 21.1% in the control group; P <0.001) and neurological outcomes (modified Garcia score: 12.1±0.5 in the ceria nanoparticles group versus 4.4±0.5 in the control group; P <0.001) of the animals with SAH. Conclusions—: Ceria nanoparticles, totally synthesized in aqueous phase using aminocaproic acid, demonstrated promising results against SAH via potent antioxidative, neuroprotective and anti-inflammatory activities. Given the obvious limitations of current therapies for SAH, ceria nanoparticles can be a potential therapeutic agent which might result in a paradigm shift in SAH treatment. Abstract : Supplemental Digital Content is available in the text.